Perspective on the Immorality of Honor Killings – A Review Article (Medico Legal Update, 2020)
The killing of a family member, when the offenders believe that the victim’s activities have resulted in immense dishonor to the family or community is called honor killing or shame killing. The absence of systematic data collection in most countries has resulted in lack of clarity on the judicial approach and its consequences, with many of the killings being reported falsely as suicides or accidental deaths by the families. Honor killings are prevalent all over the world, with the majority of them happening in the Asian countries, closely followed by the Middle East and South Asia regions. This review article attempts to analyze the present legal status of honor killing in the country of India, predominantly in the southern states.The sensational killing of a Dalit youth, Gokulraj in 2015 found in the company of a girl belonging to the Gounder community at a temple in Tiruchengode , sent shock waves across the state. Another prominent case occurred in the state of Tamil Nadu, where the marriage of Ilavarasan – a Dalit youth from Dharmapuri to a Vanniyar girl from Sellangottai, evoked deep conflicts in 2013, that lead to the former’s body lying on a railway track. With the ideals of ‘honor’ and ‘disgrace’ being deeply rooted in the Indian mindset, the laws alone will not suffice to curb such forms of violence and it has to be addressed as a sociological issue.